Unequal Exchange: Key Issues for the Labor Theory of Value. Issue 2 (2nd July 2020) - Finger, Barry
Abstract : Arghiri Emmanuel pioneered the theory of Unequal Exchange—the imperialism of trade—as an explanation for the persistence of underdeveloped economies in the 1960s. But the theory also claims to provide a robust explanation for the abandonment of revolutionary politics by metropolitan working classes, who, in the most extreme versions of this theory, no longer constitute an exploited class. It has remained somewhat dormant as a key to modern imperialism until recently revived in the work of Zak Cope and John Smith, who link this to the emergence of global production chains. What makes this theory so compelling is that it draws on commonly held, but rarely re-examined, consensus understandings of the operations of the law of value much of which has to be unraveled and reconstructed before the fundamental flaws in this thesis can be revealed. This requires a fresh look at the problems of abstract labor, the transformation problem, skilled labor and role of international monetary exchanges for the operation of the law of value.